Garcinia Mangostana Peel Extract as Sustainable Fuel Source on Ceria Synthesis under Hydrothermal Condition - SALPRIMA YUDHA S; Morina Adfa; Aswin Falahudin; Deni Agus Triawan; Liana Wahyuni; Meka Saima Perdani (Chemistry Department, The University of Brawijaya, 2019)
Cerium (IV) oxide or ceria (CeO2) was fabricated by heating an aqueous extract of Garcinia mangostana and cerium (III) nitrate in hydrothermal autoclave reactor at 200 °C for 3 hours, followed by calcination at 600 °C for 5 hours. The powder X-ray diffraction (XRD) pattern of the precipitate from cerium(III) nitrate under hydrothermal reaction conditions shows no clear XRD peaks, indicating its amorphous nature. In contrast, the products from the calcinated samples exhibit XRD peaks, which correspond to cubic fluorite structure with an average crystal size of 7.55 nm. The elemental mapping using the energy-dispersive X-ray (EDX) analysis reveals the main elements present were cerium and oxygen, with minor impurities in low amounts. The presence of Garcinia mangostana extract is predicted to be the key component and fuel source to obtain CeO2 particles with narrow crystal size.